A new experiential learning electromagnetism-like mechanism for numerical optimization - Tan J.D.; Dahari M.; Koh S.P.; Koay Y.Y.; Abed I.A. (Elsevier Ltd, 2023)
Decision making; Population statistics; Decision-making mechanisms; Electromagnetism-like mechanism algorithms; Electromagnetism-like mechanisms; Experiential learning; Exploitation; Meta heuristics; Numerical optimizations; Optimization techniques; Optimization